2010
DOI: 10.4314/jasem.v13i3.55346
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water potential on some active forms of phosphorus in a calcareous soil amended with sewage sludge

Abstract: Immobilization and mobilization reactions of soil phosphorus depend on biological properties of soil and these soil properties strongly depend on the soil water potential. The objective of this study was to test the effects of water potential on some active forms of soil P. A semiarid soil classified as Calcic Haploxerept was treated with raw sewage sludge at a rate of 20 g kg -1 . Water potentials established for soil incubation were: saturation (SA, 0 bar), field capacity (FC, -0.3 bar), and permanent wiltin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…The favourabe effect of organic materials (MMS and ML) may be to the positive effect of these materials on soil reaction and increasing the available moisture content and hence increasing the availability of P in the soil solution and it increases microbial population and P immobilization. This finding agreed with those obtained by Rady et al (2015) ; Sinegani and Mahohi (2009) ;Adekiya et al (2017) and Merwad, (2017).…”
Section: Available Phosphorussupporting
confidence: 94%
See 1 more Smart Citation
“…The favourabe effect of organic materials (MMS and ML) may be to the positive effect of these materials on soil reaction and increasing the available moisture content and hence increasing the availability of P in the soil solution and it increases microbial population and P immobilization. This finding agreed with those obtained by Rady et al (2015) ; Sinegani and Mahohi (2009) ;Adekiya et al (2017) and Merwad, (2017).…”
Section: Available Phosphorussupporting
confidence: 94%
“…The decrease in available P level after 150 days in tested soils may be attributed to assimilation by microorganisms. This finding agreed with those obtained by Sinegani and Mahohi, (2009) who reported that the addition of sewage sludge increased available P in calcareous soil after 60 and 90 days of incubation.…”
Section: Fig3 Available Phosphorus (Mg Kg -1 ) In Different Soils Asupporting
confidence: 93%
“…Increasing the amount of irrigation water increased the grain and straw yield of corn. Sinegani and Mahohi (2009) found that soluble P was higher in soil incubated in FC as compared to those incubated in other moisture(sat,0 bar), field capacity (FC,-0.3 bar),and permanent wilting point (PWP,-15 bar). Al-Oud (2011) indicated that the availability of P from rock phosphate was increased by increasing incubation period up to 90 days in calcareous soil.…”
Section: Soil and Water Sciencementioning
confidence: 92%
“…Actually, the behavior of phosphorus in soils also depends on the rates of phosphatic fertilizer, the nature and rates of applied organic manures as well as the combination of phosphatic fertilizer with organic manures as solid and liquid forms. Sinegani and Mahohi (2009) studied the effect of incubation time on soil available P, miocrobial P easily soluble and dicalcium phosphate contents. They reported that soil available P significantly decreased from 36.52 mg kg -1 to 32.09 mg kg -1 in 20 days of incubation in sewage sludge treated soil.…”
Section: Introductionmentioning
confidence: 99%